Patient with typical carcinoid initially diagnosed as high-grade neuroendocrine carcinoma. (November 2017) - Warsch, Sean; Jahanzeb, Mohammad
We report the case of a patient initially diagnosed with a high-grade neuroendocrine carcinoma, which 5 years later was determined to have a low-grade typical carcinoid. The patient received radiotherapy and numerous chemotherapy regimens for treatment of a high-grade metastatic mixed large and small cell neuroendocrine carcinoma, without a significant response to any treatment. Subsequent imaging revealed widely metastatic disease and computed tomography-guided biopsy demonstrated a carcinoid tumor with no necrosis. The patient was started on temozolomide + capecitabine, long-acting octreotide and denosumab, with everolimus planned upon disease progression. Findings from this case study highlight the importance of accurate histopathologic classification of thoracic neuroendocrine tumors at diagnosis, to avoid the unnecessary administration of aggressive chemotherapy to patients with low-grade tumors.